PENGARUH PENAMBAHAN Cu PADA CAIRAN Al Sn TERHADAP KEKERASAN LAPISAN INTERFACE KRUSIBEL BAJA - Andi Priyanto; Dody Prayitno (President University, 2017)
Steel is often used as crucial in the world of metal casting. This study aims to determine the effect of aluminum alloy fluid on the hardness of the crucible steel interface. The method begins with melting aluminum, copper, and tin according to each variant with a temperature of 700oC, then stirring on the liquid for 15 minutes and holding it for 30 minutes. From this research it is concluded that the addition of Cu (10% and 20%) in Al-Sn-Cu fluid causes hardness value at the interface layer area but the increase is not very significant.